2022
DOI: 10.1002/ese3.1084
|View full text |Cite
|
Sign up to set email alerts
|

Selection of the ultimate perovskite solar cell materials and fabrication processes towards its industrialization: A review

Abstract: Hybrid organic-inorganic perovskite materials have become one of the most studied classes of light-harvesting materials due to their exceptional properties such as high light absorption, long carrier diffusion lengths, bandgap tuning and defect tolerance. Since 2009 that the scientific community has been working on improving the power conversion efficiency (PCE) of perovskite solar cell devices, reaching now an impressive value of 25.5%. Moreover, efficiencies over 18% are often reported by several authors. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 244 publications
(459 reference statements)
0
9
0
Order By: Relevance
“…In this frame, it is observed that record cells might not share the same encapsulation strategies as more realistic, large surface cells and modules, [116] both for aging and safety reasons. [117,118] All perovskite tandem cells are even more challenging from the point of view of fabrication, [119,120] but are also very promising since they combine the potential of perovskite based cells and modules with high yields.…”
Section: Conclusion -Perspectivesmentioning
confidence: 99%
“…In this frame, it is observed that record cells might not share the same encapsulation strategies as more realistic, large surface cells and modules, [116] both for aging and safety reasons. [117,118] All perovskite tandem cells are even more challenging from the point of view of fabrication, [119,120] but are also very promising since they combine the potential of perovskite based cells and modules with high yields.…”
Section: Conclusion -Perspectivesmentioning
confidence: 99%
“…Metal halide perovskites (MHPs) have aroused fascinating research interest since the first perovskite solar cell was demonstrated, and the performance of single-junction perovskite solar cells (PSCs) has been rapidly improved with the photoelectric conversion efficiency (PCE) over 25%. [1,2] In the meantime, MHPs have emerged as promising optoelectronic materials for implementation in detectors, lasers, and light-emitting diodes (LEDs), [3][4][5][6][7][8] due to their unique optical and electronic properties such as ambipolar charge transport, [9,10] broadly tunable optical bandgap, [11,12] long carrier diffusion length, [13] high charge carrier mobility, [14] ultralong carrier lifetimes, [15,16] near-unity photoluminescence quantum yield (PLQY), [17] and extraordinarily defect tolerance. [18,19] In recent years, huge research efforts have been made with respect to enhance the environmental stability and device performance of MHPs using various methods, including surface/interface engineering, [20][21][22][23] composition/crystalline structure optimization, [24,25] and defects engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The advancements in the perovskite solar cells (PSCs) in the last decade have led to the astonishing rise in its power conversion efficiency (PCE) from 3.8% to 25.5% 1 . This increase in efficiency is driven by optimizing perovskite absorber layer composition and improvements in device architecture and processing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The advancements in the perovskite solar cells (PSCs) in the last decade have led to the astonishing rise in its power conversion efficiency (PCE) from 3.8% to 25.5%. 1 This increase in efficiency is driven by optimizing perovskite absorber layer composition and improvements in device architecture and processing techniques. This emerging third-generation solar cell technology has several other advantages: low-temperature processing, vacuum-free solution processability, and compatibility with existing industrial printing techniques, including screen-printing, blade-coating, and roll-to-roll printing.…”
Section: Introductionmentioning
confidence: 99%